Evaluating the Efficiency of Microeconomic Empowerment Programs through Econometric Matching Approaches - Nova Yuningrat (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study aims to evaluate the effectiveness of microeconomic empowerment programs using an econometric matching approach, with a focus on increasing participants' income and welfare. Microeconomic empowerment programs in Indonesia have become the primary strategy for overcoming poverty and enhancing the quality of life for the community, particularly in the microbusiness sector. This study employed a qualitative research design, incorporating interviews, questionnaires, and observations at two research locations in Bogor Regency and Bantul Regency. The study's results indicate that this program has a positive impact on participants with more established businesses, resulting in an average income increase of approximately 30%. However, participants who are just starting a business experience difficulties in making optimal use of training and capital assistance. The evaluation of this program also revealed that the training materials need to be adjusted to the type of business run by the participants, as well as the need for post-program support to ensure business sustainability. The use of econometric matching is effective in reducing selectivity bias and providing more accurate estimates of program impact. This research offers recommendations for program adjustments that are more closely aligned with the needs of participants, as well as the importance of post program mentoring in strengthening the longterm impact.